Improved Optical Properties of Nonpolar AlGaN-Based Multiple Quantum Wells Emitting at 280 nm - Jianguo Zhao; Jiangyong Pan; Bin Liu; Tao Tao; Daihua Chen; Xianjian Long; Zhe Chuan Feng; Jianhua Chang (IEEE Photonics Journal)
The optical properties of nonpolar AlGaN multiple quantum wells (MQWs) emitting at 280 nm were investigated intensively using temperature-dependent and time-resolved photoluminescence spectra associated with the characterization of structural properties. The densities of superficial pits and basal-plane stacking faults (BSFs) were reduced by 33.8% and 35.9%, respectively, for nonpolar AlGaN MQWs due to the carefully optimized dual nitridation. It was found that the nonpolar MQWs emission can be significantly improved by reducing the BSFs density as the BSFs emission was the main competing channels. Moreover, an internal quantum efficiency of 39% for nonpolar Al0.43Ga0.57N MQWs at emission wavelength of 279 nm was achieved even the full width at half maximum values of X-ray rocking curves were 0.565° for c-direction and 0.797° for m-direction. This fact means that a highly efficient deep ultraviolet light sources can be expected by means of nonpolar AlGaN due to the elimination of quantum confined Stark effect induced the decrease in radiative lifetime.